SENSITIVITY OF THE JUICE OF KAFFIR LIME FRUIT (Citrus hystrix) AGAINST BACTERIA Aeromonas hydrophila - Sihombing, Jefry Maju Arytha; Lukistyowati, Iesje; Riauwaty, Morina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT               Disease that often develops in aquaculture is one of them is red spot disease.This disease is often calledMotile Aeromonas Septicemia (MAS) caused by Aeromonas hydrophila. Alternative ingredients that can be used as prevention or treatment of fish diseases arekaffir lime plant (Citrus hystrix) which is antibacterial and antimicrobial.This research was conducted in February - June 2018 in the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine, University of Riau. The purpose of this study was to determine the sensitivity of the juice of kaffir lime to inhibit the growth ofAeromonas hydrophila bacteria, dosage of Minimum Inhibitory Concentration (MIC), and continued the LD50test obtained from the MIC dose where the test of LD50solution of kaffir lime on catfish (Pangasius sp.) by immersion. The research method used was the experimental method, for the sensitivity test using the Kirby Bauer disc method with the concentrations used were 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10% , 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.9%, 0.8%, 0.7%, 0.6% and controls ( Oxytetracycline). The results showed that the juicce of kaffir lime was able to inhibit the growth of A. hydrophila bacteria starting from doses of 100% - 0.6% with an average diameter of inhibition zones ranging from 23.03 - 6.68 mm. The dose of Minimum Inhibitory Concentration (MIC) juice of kaffir lime fruit is 0.7% with an average number of colonies of 289.33 CFU / mL. The test results of LD50 juice of kaffir lime (C. hystrix) on catfish (Pangasius sp.) By immersion method for 24 hours were at a concentration of 0.791%. Keywords:C.hystrix, Motil Aeromonas Septicemia, Kirby Bauer discs, Minimum                    Inhibitory Concentration (MIC), LD50